OP0251 Troponin T in Systemic Sclerosis: A Biomarker of Cardiac Involvement and Disease Severity. (10th June 2014) - Bosello, S.L.; De Luca, G.; Parisi, F.; Correra, M.; Capacci, A.; Berardi, G.; Canestrari, G.; Rucco, M.; Ferraccioli, G.
Abstract : Background: Heart involvement is common in Systemic Sclerosis (SSc), even though it is often clinically silent, and represents one of the leading causes of death in these patients. Objectives: The aim of the study was to define the role of troponin T (TnT) in the identification of a subclinical cardiac involvement and to correlate these levels to cardiac function and disease characteristics. Methods: Cardiac enzymes were measured at least twice in 200 consecutive SSc patients (mean age: 58.7±13.9 years; mean disease duration: 11.1±9.0 years; diffuse disease: 38.0%; anti-Scl70 positivity: 45.5%) from 2008 to 2013. Data regarding disease subtypes and organ involvement were available for the entire cohort and all patients underwent: electrocardiogram (EKG), echocardiogram and pulmonary function test (PFTs). All SSc-related death were registred. Results: Troponin T (TnT) levels were above the normal limit in 79 (39.5%) SSc patients (mean levels in positive patients:0.06±0.08 ng/ml), while only 42 patients (21%) presented raised CK-MB levels and 27 patients (13.5%) had an increase of NT-proBNP>600 pg/ml. The increase of TnT levels was associated with diffuse skin involvement and myositis (p<0.0001; p=0.006 respectively) and directly correlated with skin score (R=0.27; p<0.0001). Patients with high TnT levels presented a lower ejection fraction (59.5±9.3%) and an higher pulmonary artery systolic pressure on echocardiography (37.7±16.8 mmHg) compared to patients with normal TnT values (63.1±4.1%, p=0.04;28.3±6.8 mmHg, p<0.0001).These patients, furthermore, more frequently presented right bundle brunch block and/or fascicular heart block on EKG with respect to patients without increase of TnT (34.7% vs.10.5%; p<0.0001).Patients with high TnT levels had a more impaired lung function (DLCO 46.2±23.7%, FVC 88.3±22.5%, TLC 82.5±18.0) compared to patients with normal TnT (DLCO 56.1±22.3%, FVC 99.9±23.4%, TLC 93.2±19.3) (p<0.0001 for all comparisons). Interestingly, avascular areas at nailfold capillaroscopy were more frequently present in patients with high TnT levels compared to patients with normal TnT values (68.7% vs.46.9%; p=0.003). Moreover, TnT levels directly correlated with activity and severity indices (R=0.31; p<0.0001 for both correlations), C-reactive protein levels (R=0.31; p<0.0001), NT-proBNP and CK-MB (R=0.4; p<0.0001). During our follow-up, 16 SSc-related death occurred and 10 of these were directly related to cardiac involvement (sudden cardiac death or heart failure). All dead patients presented increased TnT levels. None of the patients with normal TnT values died for cardiac complications. At multivariate analysis, NT-proBNP >600 pg/ml (RR=12.6, CI=2.6-60) and troponin T>0.014 ng/ml (RR=9.5, CI=1.1-89) emerged as independent predictors of SSc-related death. Conclusions: Our data suggest that subclinical myocardial involvement is more relevant in Scleroderma disease than appreciated previously, as revealed by the frequent detection of high TnT levels in SSc patients, especially in those with a more aggressive disease. As supported by the presence of a more impaired systolic function and more frequent EKG abnormalities in SSc patients with high TnT levels, this cardiac enzyme can be considered a useful biomarker of cardiac damage and a prognostic biomarker of cardiac-related death. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4477